ADAKAH PENGARUH FINANCIAL CONDITION, FINANCIAL PERFORMANCE, GROWTH, AND RECEIVABLE/INVENTORY TERHADAP PENDETEKSIAN KECURANGAN LAPORAN KEUANGAN? - PUTRI VIRGONIA PUSPI, HARDIYANA Putri Virgonia (Jurnal Akuntansi AKUNESA, 2012)
The purpose of this research is to find the influence of financial conditions, financial performance and rapid growth is an important part in the detection of financial statement fraud on a large scale company. This study investigated the usefulness of annual financial reporting published in idx. This research method is a method of associative quantitative. Binary logistic regression used implementation of detection. Based on related research review has been conducted, the results of this research show that a significantly impact on ROA detection of fraudulent financial reporting in many companies.Keywords: fraud, auditing standard, financial statement fraud, fraud detection methodsPENDAHULUAN